Outdoor Study dalam Pembelajaran Ekonomi Koperasi Berbasis Koperasi Produksi dan Konsumsi - Annisya Annisya; Lustina Fajar P (Jurnal Pendidikan Ekonomi, 2022)
The purpose of this research is to increase knowledge and understanding of the material in cooperative economics courses through the outdoor study method. This type of research is development research using the ADDIE method. Based on the results of research conducted on the discussion and results, it can be concluded that the application of the outdoor study method in cooperative economics learning can increase students' knowledge and understanding of the material in cooperative economics courses. The use of this method can also make learning activities into meaningful learning. The final result obtained is that students get scores in the range of 80-95 with information that is very good and satisfactory in completing their assignments and knowledge in the field of cooperatives.DOI: https://dx.doi.org/10.17977/UM014v15i22022p135